PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI MANAJEMEN,INFORMASI AKUNTANSI MANAJEMEN DANPELAYANAN SISTEM INFORMASI TERHADAP INTENSITAS PENGGUNAAN DAN KEPUASAN PENGGUNASERTA DAMPAKNYA TERHADAP KINERJA PENGAMBILAN KEPUTUSANMANAJEMEN OPERASIONAL (Survei pa - Heni Nurani Hartikayanti (Indonesian Journal of Economics and Business, 2011)
The type of research used in this research is descriptive verificative and explanatory survey. The sampling technique used was simple random sampling in 22 hospitals PPK-BLU. The number of respondents who returned questionnaires is  408 respondents. Technique of data collecting is done by using questionnaires and interviews. Analysis of the data used is Path Analysis with Lisrell 8.70.        The results of this study revealed: 1) There is a fairly close relationship with the positive direction between the quality of management accounting information systems, management accounting information quality and service quality of  information system, 2) The quality of accounting information systems management, management accounting information quality and service quality of  information system have a significant effect, either simultaneously and partially on the intentions to  use of information systems; 3) The quality of accounting information systems management, management accounting information quality and service quality of  information system have a significant effect, either simultaneously and partially on the users satisfaction of information systems; 4) There is fairly close relationship  between the intentions to  use of the information system and users satisfactionof information systems; 5) Intentions to use of information systems and users satisfaction information system have a significant effect, either simultaneously or partially on performance operational management decision-making.